Impact of gestational weight gain in diabetic mothers on maternal and fetal outcomes at delivery - Aziz, Effat; Sultana, Tasnia; Islam, Shahidul; Akter, Salma; Sarmin, Rubab; Tasnim, Maliha; Husain, Mahzabin; Chowdhury, Jannatul Ferdous (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Adequate weight gain during pregnancy is crucial for healthy outcomes, while excessive weight gain is linked to adverse effects, including higher rates of cesarean sections, gestational diabetes, and complications during delivery. The aim of this study was to assess the impact of gestational weight gain on maternal and fetal outcomes in women with pregestational and gestational diabetes at delivery. Methods: A cross-sectional study was conducted in the obstetrics and gynecology department of BIRDEM General Hospital-II, Dhaka during January 2023-June 2024. A total 102 pregnant women with pregestational diabetes and gestational diabetes mellitus (GDM) were consecutively selected from patients admitted after 37 weeks of gestation and divided in to GDM (n=51) and PGDM (n=51) groups. Results: Among GDM patients, 49.0% had normal GWG, 31.4% excessive, and 19.6% inadequate, while in PGDM patients, 37.3% had normal, 37.3% inadequate, and 25.5% excessive GWG. Maternal complications occurred in 43.8% of GDM and 61.5% of PGDM mothers, with no significant difference. Fetal complications were comparable across GWG groups. Notably, newborns of PGDM mothers with normal GWG had higher rates of SGA and NICU admission compared to GDM, whereas normal birth weight was more common in GDM (p=0.014). Conclusions: In GDM patients, excessive weight gain was linked to significantly higher cesarean section rates and while PGDM cases showed more fetal and maternal complications than GDM but not significant. However, most newborns had normal birth weights across all groups, and many outcomes did not differ significantly.